HUBUNGAN POLA ASUH ORANG TUA DAN LINGKUNGAN TEMAN SEBAYA DENGAN KESEHATAN MENTAL REMAJA DI SMA NEGERI 2 MAJALENGKA TAHUN 2023 - Maula, Yusrina Ni'mal; Lina, Nur; Neni, Neni (Jurnal Kesehatan Komunitas Indonesia, 2023)
Mental health problems in Indonesia are dominated by teenagers. The results of the 2022 Indonesia-National Adolescent Mental Health Survey (I-NAMHS) state that one in three or 34.9% of adolescents experience mental health problems. Adolescence is one of the factors that have an influence on mental health. The aim to analyze the relationship between parenting style and peer environment with adolescent mental health at SMA Negeri 2 Majalengka in 2023. Methode of the research is cross-sectional methode. The sampling technique usedÂ  proportionate stratified random sampling. The population in this study were students of SMA Negeri 2 Majalengka, totaling 863 students. The samples studied were 273 samples. The instruments used were the Strength and Difficulties Questionnaire (SDQ) and the parenting style questionnaire. Data analysis used the Pearson Chi-Square Test. Results: The p-value between parenting style and adolescent mental health is 0.030 0.05. The p-value between peer environment and adolescent mental health is 0.000 0.05. Conclusion: There is a significant relationship between parenting style and peer environment and adolescent mental health at SMA Negeri 2 Majalengka in 2023. Suggestion: Counseling can be done for students regarding mental health and peer environment which can be done by the school or doing work together with the Munjul Health Center and can carry out periodic seminars or directions to parents of students regarding the importance of maintaining communication with children, children's mental health, or overall parenting.